Health Education about Preparation of Exclusive Breastfeeding for Pregnant Women - Firawati, Firawati; Hasnaeni, Hasnaeni; Kasim, Jamila; A, Alfiah; Kadrianti, Erna (Lembaga Riset dan Inovasi Masyarakat Madani, 2023)
Mother's Milk is the ideal food for the growth and development of babies. in Indonesia the coverage of exclusive breastfeeding is still far from the national target of 80%, health education activities for pregnant women related to knowledge about exclusive breastfeeding, the benefits of breastfeeding for babies and mothers, nutritional and psychological preparation and practicing proper breastfeeding being solution The right way to prepare yourself from the start so that pregnant women can provide exclusive breastfeeding, his community service is carried out at the Bara-Baraya Community Health Center, Makassar City. The service method is interactive participation accompanied by lectures, questions and answers, discussions, and roleplay. As a result of this service, we get enthusiastic pregnant mothers who actively ask questions, so they are committed to providing exclusive breast milk to their babies, thus this health education is an effective effort to increase knowledge among pregnant women. It is recommended that health workers can carry out health education on an ongoing basis considering that there are still pregnant women who have insufficient knowledge about the importance of preparing for exclusive breastfeeding.